PERANCANGAN KOMUNIKASI VISUAL FOTOGRAFI PRODUK MAKANAN KERIPIK PISANG LENANA DI PT. SDS VISUAL, DENPASAR - Dylan Birtano, Bimo; Sarjani, Ni Ketut Pande; Artawan, Cokorda Alit (Program Studi Desain Komunikasi Visual, 2024)
This study aims to examine the process of visual communication design for the food product photography of Lenana Banana Chips carried out by PT. SDS Visual in Denpasar. The research identifies the stages in visual design, starting from direction, idea generation, and concept illustration, to the process of shooting and photo editing. The research method used is a case study with a qualitative approach. The results show that PT. SDS Visual uses a structured approach in each design stage to ensure professional and attractive results. These findings provide insights into the importance of visual design in enhancing product appeal and strengthening marketing strategies. In conclusion, a systematic and collaborative design process is key to success in the visual communication of food products. This study suggests that other companies can adopt a similar approach to achieve optimal results.